The functional activity of donor kidneys is negatively regulated by microribonucleic acid-451 in different perfusion methods to inhibit adenosine triphosphate metabolism and the proliferation of HK2 cells. Issue 5 (2nd May 2022) - Zhu, Xu-Hui; Han, Long-Xi; Zhang, Rong-Jie; Zhang, Peng; Chen, Fu-Gang; Yu, Jia; Luo, Heng; Han, Xiu-Wu
ABSTRACT: This study explored the regulation of different perfusion methods on ischemia-reperfusion injury in donor kidneys. In this study, renal cortical/medullary tissue specimens were collected from porcine kidneys donors using different perfusion methods at various time points. Hematoxylin and eosin (H&E) staining was used to test the histological differences. Differentially expressed micro-ribonucleic acids (miRNAs) were identified by miRNA transcriptome sequencing. Reverse transcription-polymerase chain reaction (RT-PCR) tests were used to verify the changes in miRNAs in the kidney tissue taken from different perfusion groups. The related signaling pathways and the changes in the cell functions of different perfusion groups were analyzed by Kyoto Encyclopedia of Genes and Genomes (KEGG) /Gene Ontology (GO) bioinformatics analyses. The effects of miRNA overexpression on the metabolism and proliferation of HK2 cells were detected by ATP kit and MTT assay. The H&E staining results showed that there were essentially no differences in the tissue samples among different perfusion groups at and before 12 h compared with a control group. The quantitative PCR results revealed that there was essentially no change in the expression of ssc-miR-451, ssc-miR-1285, and ssc-miR-486 in the cis infusion or joint infusion kidney groups, and their expression was significantly down-regulated over time in the trans-infusion kidney group. The bioinformatics analysis showed that the cellular component, molecular function, and biological processes of the kidney tissue, which had been perfused using three methods, had been consistently affected. The most significant changes after perfusion occurred in the intracellular metabolism signaling pathways. Furthermore, the energy metabolism and proliferation of the HK2 cells were significantly inhibited after the overexpression of miR-451. Specific miRNA markers, such as miR-451, may play a negative regulatory role in cell metabolism following the perfusion of kidney transplants using different methods. Graphical abstract: uf0001